2018
DOI: 10.1021/acssuschemeng.8b03645
|View full text |Cite
|
Sign up to set email alerts
|

Decorating CeO2 Nanoparticles on Mn2O3 Nanosheets to Improve Catalytic Soot Combustion

Abstract: Herein, we synthesized CeO2 nanoparticles-decorated Mn2O3 nanosheets on monolithic Ni foam (Ce/Mn-NF) for catalytic elimination of soot particulates. The macroporous nanostructures created by the Mn2O3 nanosheets improve the soot-catalyst contact efficiency on the external surface of catalysts. The superficial Mn–Ce interaction can produce Mn4+ and oxygen vacancies on the Ce/Mn-NF catalysts through the redox process of Ce4+ + Mn3+ ↔ Mn4+ + Ce3+, simultaneously generating surface active oxygen species. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…The peaks at binding energies of 640.9 and 642.0 eV are correlated with the existence of Mn 2+ and Mn 3+ , respectively. 48,49 The other peak at 646.0 eV is attributed to the satellite peak. 48,50 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks at binding energies of 640.9 and 642.0 eV are correlated with the existence of Mn 2+ and Mn 3+ , respectively. 48,49 The other peak at 646.0 eV is attributed to the satellite peak. 48,50 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…48,49 The other peak at 646.0 eV is attributed to the satellite peak. 48,50 Fig. 5D shows the O 1s spectra of the samples, which are fitted to three peaks (529.2, 531.3 and 533.9 eV), which are assigned to the lattice oxygen, the chemisorbed oxygen and the physically adsorbed H 2 O, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature-programmed reduction of hydrogen was used to study the redox properties of MnO x , and the results are displayed in Figure A. MnO x -N shows three reduction peaks: the reduction of MnO x to Mn 2 O 3 at 340 °C (peak I), the reduction of Mn 2 O 3 to Mn 3 O 4 at 434 °C (peak II), and the reduction of Mn 3 O 4 to MnO at 497 °C (peak III) . After modification by BP, the reduction peaks shift to a lower temperature, possibly owing to a smaller average particle size of MnO x .…”
Section: Resultsmentioning
confidence: 99%
“…Among the transition metals doped catalysts, Mn-based catalysts are widely used in the field of environmental catalysis [17,18]. It is reported that Mn-dopedCeO 2 has been applied in the abatement of contaminants, such as the catalytic reduction of NO and diesel soot combustion, which exhibit excellent catalytic activity [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%